Attitudes of Teachers Regarding the Inclusion of Parents in the Educational Process of Students - Haskaj A.; Chichevska Jovanova, Natasha (Faculty of Philosophy, University of Tetova, Republic of Macedonia, 2020)
Parental involvement is an integral variable that has a considerable value in the overall educational achievement and student learning process. Family-school and parent-teacher cooperation contributes to child/student development, promotes the work of the teacher, strengthens the role that the parents have in the development, upbringing and education of their child. The need for active involvement of parents in the partnership with the school, stems from the fact that parents are the first educators, teachers, who can give the teachers the most useful information that will be the basis for directing and undertaking future joint actions for the benefit of each child/student. Partnership, i.e. fostering co-operation is a challenge for every teacher who is trying to pave the way to create conditions, forms, and means for realization of constructive cooperation. The school's collaboration with parents begins in the early years of schooling and accompanies the student throughout his entire school experience. The positive relation between parents and schools affects the behavior and success of children at school. Families can also play an important role in the process of promoting laws and policies for inclusive education.
Keywords: involvement, parent, school, partnership, student